History as Seen Through Postcards: A Story of the Lodz Ghetto—Total Isolation - Davidovitch, Nitza; Ben Ishay, Shlomit; Dorot, Ruth (Journal of Education Culture and Society, 2022)
Thesis. This study explores the role of postcards as a historical, documentary, and artistic source depicting the events of the Holocaust, focusing on postcards written or received by inhabitants of the Lodz Ghetto. 78 postcards were translated into Hebrew and on exhibition at the Holocaust and Heroism Memorial Museum in Israel. Research indicates that the postcards served as an authentic and rare source of information as well as understanding the emotions of Jews whose lives were overshadowed by the threat of annihilation.Methods. The study is a qualitative one, based on the grounded theory approach. Analysis is established on identifying and characterising recurrences in the raw material of findings, with a clear definition of the unit of analysis, to build a hierarchy of the recurrences and themes, and to construct a theoretical model that explains the reality under investigation. Researchers in this method gather information about the life patterns of their subjects as well as the organizational and social structures. Grounded theory assumes that all people who have shared life circumstances also have shared social and psychological patterns, which even if not consciously formulated or expressed grow from the shared experiences.Results and conclusion. In-depth analysis reveals the historical events from the perspective of the postcard writers, as they experienced them in the ghetto. The postcards sent to the ghetto by relatives and acquaintances reveal their writers’ hopes of reuniting with their family or their extreme despair as they cope with the loss of their family.